The horizon effect of stock return predictability and model uncertainty on portfolio choice: UK evidence - Guangjie Li (Cardiff University, Cardiff Business School, 2009)
We study how stock return's predictability and model uncertainty affect a rational buy-and-hold investor's decision to allocate her wealth for different lengths of investment horizons in the UK market. We consider the FTSE All-Share Index as the risky asset, and the UK Treasury bill as the risk free asset in forming the investor's portfolio. We identify the most powerful predictors of the stock return by accounting for model uncertainty. We find that though stock return predictability is weak, it can still affect the invesor's optimal portfolio decision over different investment horizons.
Keywords: C11; G11; G15; 330; stock return predictability; portfolio choice; Bayesian Model Averaging; SUR model; Kapitalertrag; Prognoseverfahren; Portfolio-Management; Bayes-Statistik; Theorie; Großbritannien